2016
DOI: 10.4269/ajtmh.15-0868
|View full text |Cite
|
Sign up to set email alerts
|

Artemether–Lumefantrine Concentrations in Tablets and Powders from Ghana Measured by a New High-Performance Liquid Chromatography Method

Abstract: Abstract. We developed and validated a new analytical method for the simultaneous quantification of artemether and lumefantrine in fixed-dose tablets and powders for reconstitution into pediatric suspensions (PSs). The method showed linearity (r 2 > 0.9947), precision (coefficient of variation < 2%), accuracy (deviation of mean from actual concentrations < 4%), and specificity (peak purities > 99%). The validated method was used to analyze 24 batches of fixed-dose tablets and PSs of artemether and lumefantrine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…The suitability of Prosochit ® in enhancing oral delivery of artemether is in consonance with the work of Ngwuluka et al (2015) which showed that combination of two polymers is often superior to the individual ingredient. Previous work showed that PRG caused delayed release of artemether but enhanced permeation compared to acacia gum (Olorunsola et al, 2017), whereas dissolution is the rate-limiting step for the absorption of the drug (Rosenthal, 2004).…”
Section: Tablet Propertiessupporting
confidence: 71%
See 2 more Smart Citations
“…The suitability of Prosochit ® in enhancing oral delivery of artemether is in consonance with the work of Ngwuluka et al (2015) which showed that combination of two polymers is often superior to the individual ingredient. Previous work showed that PRG caused delayed release of artemether but enhanced permeation compared to acacia gum (Olorunsola et al, 2017), whereas dissolution is the rate-limiting step for the absorption of the drug (Rosenthal, 2004).…”
Section: Tablet Propertiessupporting
confidence: 71%
“…Different concentrations of artemether (0.05%, 0.10%, 0.15%, 0.20%, and 0.25% w/v) were prepared in 1.0-mol.l −1 ethanolic hydrochloric acid (International Pharmacopoeia, 2006) and the absorbance was taken at 210 nm (Debra et al, 2016). This was used to get the Beer-Lambert's plot for artemether.…”
Section: Evaluation Of Tablet Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…An assessment of the quality of artemether-lumefantrine preparations and artemether injections in Cape Coast Metropolis, Ghana, showed that 7 (87.5%) of the 8 brands (6 tablets, 2 suspensions) and all 2 artemether injections passed the International Pharmacopoeia content test [12]. A new validated high performance liquid chromatography method used to analyse the content of 24 artemether-lumefantrine tablets and powders for reconstitution into paediatric suspensions obtained in Ghana showed that all 4 samples which failed (16.7%) were powders for reconstitution into suspensions with two (8.3%) of the samples showing unacceptably higher levels of 222% and 756% artemether [13]. The analysis of microbial load of seven brands of multivitamin syrups marketed in Maiduguri, Nigeria, using the pour-plate method showed that one brand (14.3%) contained the pathogenic bacteria Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%
“…Literature review [7][8][9][10][11][12][13][14][15][16][17][18][19] reveals that different methods RP-HPLC, UV, LCMS for its analysis in formulations. Hence our present plan is to develop a new, sensitive, robust& accurate method for its analysis in formulation, after a detailed study, a new UPLC method was decided to be developed and validated as per ICH norms 5,6 .…”
Section: Figure1: Structures For Amt and Lftmentioning
confidence: 99%